2022
DOI: 10.1038/s41467-022-34861-x
|View full text |Cite
|
Sign up to set email alerts
|

H2A.Z deposition by SWR1C involves multiple ATP-dependent steps

Abstract: Histone variant H2A.Z is a conserved feature of nucleosomes flanking protein-coding genes. Deposition of H2A.Z requires ATP-dependent replacement of nucleosomal H2A by a chromatin remodeler related to the multi-subunit enzyme, yeast SWR1C. How these enzymes use ATP to promote this nucleosome editing reaction remains unclear. Here we use single-molecule and ensemble methodologies to identify three ATP-dependent phases in the H2A.Z deposition reaction. Real-time analysis of single nucleosome remodeling events re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…To further investigate the role of the nucleosomal acidic patch for SWR1C-mediated dimer exchange, we explored how disruption of each acidic patch impacted the nucleosome binding affinity of SWR1C for nucleosomes, leveraging a fluorescence polarization assay. Using a Cy3labeled 77N0 nucleosome, we determined a Kd of 13.6 nM for an AB/AB nucleosome (Figure 2A), similar to prior studies 61 . However, disruption of even a single nucleosomal acidic patch severely weakened SWR1C binding, such that a Kd was unable to be determined (Figure 2B-D).…”
Section: The Nucleosomal Acidic Patch Is a Key Driver Of Swr1c Bindin...supporting
confidence: 75%
“…To further investigate the role of the nucleosomal acidic patch for SWR1C-mediated dimer exchange, we explored how disruption of each acidic patch impacted the nucleosome binding affinity of SWR1C for nucleosomes, leveraging a fluorescence polarization assay. Using a Cy3labeled 77N0 nucleosome, we determined a Kd of 13.6 nM for an AB/AB nucleosome (Figure 2A), similar to prior studies 61 . However, disruption of even a single nucleosomal acidic patch severely weakened SWR1C binding, such that a Kd was unable to be determined (Figure 2B-D).…”
Section: The Nucleosomal Acidic Patch Is a Key Driver Of Swr1c Bindin...supporting
confidence: 75%
“…Reactions to measure dimer exchange by SWR1C were performed under single turnover conditions (excess enzyme to nucleosomal substrate) and contained free H2A.Z/H2B (ZB) dimers which act as an essential co-substrate. Addition of SWR1C to a wildtype nucleosome led to a rapid drop in FRET, showing the biphasic kinetics consistent with the sequential exchange of the two nucleosomal H2A/H2B (AB) dimers 44,45 . Incubation of SWR1C with a nucleosome that lacks an intact acidic patch (AB-apm/AB-apm nucleosome) showed little decrease in the FRET signal, indicating that an intact nucleosomal acidic patch is essential for SWR1C to catalyze H2A/H2B eviction (Figure 1B).…”
Section: Dimer Exchange By Swr1c Requires the Nucleosomal Acidic Patchmentioning
confidence: 64%
“…Previously, we and others reported that SWR1C preferentially exchanges the linker distal H2A/H2B dimer, as monitored by either ensemble or single molecule FRET analyses 44,47,48 . The asymmetric nucleosome substrates, harboring only a single, labeled H2A/H2B dimer were leveraged to further investigate this preferential exchange.…”
Section: Dimer Exchange By Swr1c Requires the Nucleosomal Acidic Patchmentioning
confidence: 94%
“…Single-molecule Stoichiometry Image Analysis. Channel alignment of the 532 nm and 641 nm channels was done as previously described (Fan et al, 2022). Briefly, a custom MATLAB script was used to identify fluorescent molecules in the 532 and 641 emission channels based on local maximum and particles were fit using a 2D Gaussian.…”
Section: Dna Pulldown Assaymentioning
confidence: 99%